Prevalence and Characteristics of Phenicol-Oxazolidinone Resistance Genes in Enterococcus Faecalis and Enterococcus Faecium Isolated from Food-Producing Animals and Meat in Korea - Eiseul Kim (MDPI AG, 2021)
The use of phenicol antibiotics in animals has increased. In recent years, it has been reported that the transferable gene mediates phenicol-oxazolidinone resistance. This study analyzed the prevalence and characteristics of phenicol-oxazolidinone resistance genes in Enterococcus faecalis and Enterococcus faecium isolated from food-producing animals and meat in Korea in 2018. Furthermore, for the first time, we reported the genome sequence of E. faecalis strain, which possesses the phenicol-oxazolidinone resistance gene on both the chromosome and plasmid. Among the 327 isolates, optrA, poxtA, and fexA genes were found in 15 (4.6%), 8 (2.5%), and 17 isolates (5.2%), respectively. Twenty E. faecalis strains carrying resistance genes belonged to eight sequence types (STs), and transferability was found in 17 isolates. The genome sequences revealed that resistant genes were present in the chromosome or plasmid, or both. In strains EFS17 and EFS108, optrA was located downstream of the ermA and ant(9)-1 genes. The strains EFS36 and EFS108 harboring poxtA-encoding plasmid cocarried fexA and cfr(D). These islands also contained IS1216E or the transposon Tn554, enabling the horizontal transfer of the phenicol-oxazolidinone resistance with other antimicrobial-resistant genes. Our results suggest that it is necessary to promote the prudent use of antibiotics through continuous monitoring and reevaluation.